Prevalence, duration and aetiology of bacteraemia following dental extractions - Tomás, I; Álvarez, M; Limeres, J; Potel, C; Medina, J; Diz, P (Oral diseases, 2007)
Objective:  To investigate the prevalence, duration and aetiology of bacteraemia following dental extractions, analysing the factors affecting its development. Subjects and methods:  The study group was composed of 53 patients undergoing dental extractions under general anaesthesia. Peripheral venous blood samples were collected at baseline and at 30 s, 15 min and 1 h after the dental extractions. Samples were inoculated into BACTEC PLUS aerobic and anaerobic blood culture bottles and were processed in Bactec 9240. Subculture and further identification of the bacteria isolated was performed by conventional microbiological techniques. Results:  The prevalence of bacteraemia following dental extractions was 96.2% at 30 s, 64.2% at 15 min and 20% at 1 h after completing the surgical procedure. The bacteria most frequently identified in the positive blood cultures were Streptococcus spp. (63.8%), particularly Streptococcus viridans. Conclusions:  In our series, the majority of patients undergoing dental extractions developed bacteraemia, usually of a streptococcal nature, independently of the grade of oral health and of the number of extractions performed. Positive blood cultures persisted for at least 1 h after the dental procedure in a considerable number of patients, questioning the supposedly transient nature of bacteraemia following dental extractions.